2011 IEEE International Symposium on Information Theory Proceedings 2011
DOI: 10.1109/isit.2011.6033865
|View full text |Cite
|
Sign up to set email alerts
|

Efficient message passing scheduling for terminated LDPC convolutional codes

Abstract: Abstract-Message passing schedules that reduce the decoding complexity of terminated LDPC convolutional code ensembles are analyzed. Considering the AWGN channel, various schedules are compared by means of density evolution. The results of the analysis together with computer simulations for some (3,6)-regular codes confirm that sliding window decoding is an attractive practical solution for low-latency and low-complexity decoding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 9 publications
4
37
0
Order By: Relevance
“…As noted previously, under tight latency constraints, the WD threshold can be improved by using small w; in fact, excellent WD performance has been shown for binary SC-LDPC code ensembles using repeated edges in the protograph and w = 1 [29], [30]. In the case of qary SC-LDPC code ensembles, we have also found that the case w = 1, i.e., the set of edge…”
Section: Code Ensemble Constructionsupporting
confidence: 71%
See 4 more Smart Citations
“…As noted previously, under tight latency constraints, the WD threshold can be improved by using small w; in fact, excellent WD performance has been shown for binary SC-LDPC code ensembles using repeated edges in the protograph and w = 1 [29], [30]. In the case of qary SC-LDPC code ensembles, we have also found that the case w = 1, i.e., the set of edge…”
Section: Code Ensemble Constructionsupporting
confidence: 71%
“…We are interested in searching for q-ary SC-LDPC code ensembles for which a small window size W can provide WD with a good threshold, which implies that the coupling width w should be kept small. Indeed, our results for q-ary SC-LDPC codes together with those in the literature for binary SC-LDPC codes [29], [30] show that ensembles with w = 1 provide the best latency-constrained performance with WD.…”
Section: B Windowed Decoding (Wd)supporting
confidence: 67%
See 3 more Smart Citations